AXA Banque: An evaluation of AXA Group's entry into the French banking market. - FAVROT, Camille (2009)
AXA is a French global insurance company, constituted as “a group of companies independently organized and operated according to the regulations of many different countries” (Wikipedia website, as accessed in 2009). AXA Group engages in life, health, and other forms of insurance, as well as investment management. In 2002, they decided to extend their activities to banking and bought Banque Directe out, a subsidiary of BNP Paribas, in order to create AXA Banque in April 2003. Here it seems interesting to study this move from AXA onto the banking market from a marketing and strategic point of view, (hopefully) in order to give other retail financial services companies insights for further entries into the market. Why AXA Group, which is one of the biggest insurance companies in the world, decided to take such a decision and developed a new activity very different (even if linked in some ways) from its core activity? Did they implement a new marketing strategy and what were the challenges they had to face? How did they manage to compete successfully?